Literatur Review: Efektivitas Madu untuk Mengobati Luka pada Pasien Diabetes Mellitus - Galih Noor Alivian (Journal of Bionursing, 2021)
Introduction: Diabetes mellitus is the level of glucose in the blood excess, which is caused by disruption of secretion or work of insulin hormone. Diabetics in Indonesia ranks fourth after India, China, United States. Diabetes mellitus lesions can be treated using honey, this supports the belief of the people of Indonesia about honey can cure all diseases. Method: Journal search is done electronically using database, they are: Google Scholar, Pubmed. Keywords used are honey / honey, wound / injury, and diabetes mellitus; there are 3 journals taken to create a review literature from 2010-2017. Objective: To prove the effectiveness of honey to treat patients with diabetes mellitus wound by analyzing 3 journals. Results: Honey therapy has a good effectiveness against wound healing diabetes mellitus. Discussion: The use of honey to treat wounds, effectively accelerate wound healing diabetes mellitus. Conclusion: Honey therapy effectively accelerates the healing of diabetes mellitus wounds.